Tempoyak: Nutritional Composition, Probiotic Potential, and Health Benefits of a Traditional Fermented Durian Product - A Review - Marwati Marwati; Krishna Purnawan Candra; Aswita Emmawati; Miftakhur Rohmah; Rimbawan Apriadi (Riviera Publishing, 2025)
Tempoyak is a traditional durian-based fermented product widely consumed in Indonesia and Malaysia. The spontaneous fermentation process is dominated by Lactic Acid Bacteria (LAB), mainly Lactobacillus plantarum, Lactobacillus fermentum, and Pediococcus spp., which contribute to its flavor, aroma, and functional properties. While tempoyak has been consumed for generations, research on its nutritional composition, probiotic potential, and health benefits remains limited. This review summarizes tempoyak's nutritional composition, bioactive compound content, and probiotic effects, particularly its impact on gut microbiota balance, glucose metabolism, inflammation reduction, and lipid metabolism. We found that tempoyak fermentation increases acidity, decreases sugar content, and enriches bioactive metabolites L. plantarum and P. acidilactici strains in tempoyak exhibit high resistance to stomach acid and bile salts, strong adhesion to intestinal cells, and significant antioxidant and probiotic activities. These properties suggest tempoyak supports gastrointestinal health, regulates blood glucose, lowers cholesterol, and potentially protects against cardiovascular disease. Tempoyak shows promise as a fermented functional food for metabolic and cardiovascular health, though further research is needed to confirm its mechanisms and applications in disease prevention.